Androgen Insensitivity Syndrome - Hughes, Ieuan Arwel; Werner, Ralf; Bunch, Trevor; Hiort, Olaf (Seminars in Reproductive Medicine, 2012)
The androgen insensitivity syndromes (AIS) fall within the generic category of 46,XY DSD (disorder of sex development) and present as phenotypes associated with complete or partial resistance to the action of androgens. Three categories are recognized: complete androgen insensitivity syndrome (CAIS), partial androgen insensitivity syndrome (PAIS), mild androgen insensitivity syndrome (MAIS).The androgen receptor (AR) is encoded by an 8 exon gene on the X chromosome long arm. More than 800 mutations in the AR gene have been reported in AIS patients (www.androgendb.mcgill.ca/). They are distributed throughout the gene with a preponderance located in the ligand binding domain. The most severe mutations are generally associated with a CAIS phenotype, but the correlation is less defined in PAIS. CAIS presents typically as primary amenorrhoea in an adolescent female and less commonly in infancy with bilateral inguinal/labial swellings due to testes. The differential diagnosis in CAIS is limited, whereas in PAIS, numerous other causes of DSD can also produce the typical phenotype of micropenis, severe hypospadias and bifid scrotum.Management issues in CAIS involve timing of gonadectomy, appropriate hormone replacement therapy and assessment of the need for vaginal dilation or rarely, vaginal surgery. The risk of gonadal germ cell tumor is low during childhood and adolescence but increases in later adulthood. Expert psychological counseling is mandatory to manage the disconnect between chromosomal, gonadal and phenotypic sex and to choreograph the evolving process of disclosure from late childhood through to maturity. It is implicit that management in AIS requires a multidisciplinary team and engagement with patient advocacy groups.
Keywords: androgen insensitivity; androgen receptor; mutations; germ cell tumors; hormone replacement; disclosure